Generasi Z dan Fenomena Quiet Quitting: Apakah Burnout jadi Penyebabnya? - Tita Trianita; Arif Rahman Hakim; Regi Ramadan (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Generation Z, which grew up in the digital age and is known to be adaptive yet realistic, faces high pressure in the modern workplace. In the midst of this pressure, the phenomenon of quiet quitting, which includes a decrease in worker engagement and minimum task fulfillment, is increasingly prominent. This study aims to examine the influence of burnout on the phenomenon of quiet quitting in generation Z workers. The method used in this study is a quantitative method with a cross-sectional design and involves 354 respondents of generation Z workers in Karawang obtained using convenience sampling with details of 150 male workers and 204 female workers aged 18-27 years. The research instruments used were the Oldenburg Burnout Inventory (OLBI) to measure burnout behavior and the Quiet Quitting Scale (QQS) to measure quiet quitting behavior. The results of regression analysis showed that burnout has a positive and significant effect on quiet quitting (β = 0.782, p < 0.05). Thus, an increase in burnout will increase the tendency of workers to do quiet quitting. A 61.2% variation in quiet quitting behavior can be explained by the level of burnout. This research enriches the understanding of burnout and quiet quitting in generation Z, and provides a practical basis for companies and workers in creating a healthy and productive work environment.